Pediatric Diagnostic Labs for Primary Care: An Evidence-based Approach - John, Rita Marie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook helps nurses, physician assistants, medical students and residents to order appropriate tests and understand how to interpret them to improve their diagnostic reasoning. Children are not like adults, and interpreting of the results of their diagnostic laboratory tests requires knowledge of the biochemical and metabolic differences. Using a combination of information, questions and case studies, the book allows readers to gain an understanding of the key concepts of sensitivity, specificity, and positive and negative predictive values, as well as the indications for diagnostic lab tests. This book presents the state of art in testing across body systems and guidance on how to order and interpret diagnostic laboratory tests in pediatric patients. Each chapter includes learning objectives, tables and figures, as well as questions and references for further learning. This textbook provides an update for clinicians and is a valuable learning tool for students and new clinicians. .
1. Pediatric Diagnostic Lab Tests: An Overview -- 2. Laboratory Screening and Diagnostic Testing in Antepartum Care -- 3. Care of the Newborn -- 4. The Well Pediatric Primary Care Visit and Screening Laboratory Tests -- 5. PointofCare Testing in Primary Care -- 6. Care of the Child with an Infectious Disease or Immunological Defect -- 7. Genetics and Pediatric Patient -- 8. Hematology -- 9. Care of the Child with a Gastrointestinal Disorder -- 10. Care of the Child with a Renal Problem -- 11. Care of the Child with a Pediatric Endocrine Disorder -- 12. Care of the Child with a Possible Rheumatological Disorder.
Keywords: Nursing; Pediatrics; Diagnosis; Biochemical markers; Nursing; Pediatrics; Diagnosis; Biomarkers; Pediatrics; Diagnostic Techniques and Procedures; Primary Health Care; Evidence-Based Medicine